Perayaan Sarasvati sebagai Pemuliaan Pengetahuan - Surada, I Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Sarasvati is the name one of the personifications Ida Sang Hyang Widhi Wasa as ruler of science. Sarasvati as a symbol of awareness and enlightenment has taken root and entrenched in Indonesian, manifested in various forms of religious activities, including ceremonies and ceremonies. The worship of Dewi Sarasvat means to worship and support the knowledge of high values and knowledge. Science and understanding are the most powerful weapons to drive away ignorance. SarasvatÄ« is like a torchbearer for Hindus, freeing Hindus from the darkness of mind, grief, anger which is the cause of misery. The meaning of the celebration of SarasvatÄ«, the worship of Ida Sang Hyang Widhi Wasa as Goddess SarasvatÄ«, as symbol of awareness and enlightenment, and shows that people who are Hindus are eager for science. Worshiping Dewi SarasvatÄ« means worshiping and upholding the value of science and wisdom.